Student Interaction with AI Technology and Its Impact on Digital Literacy at SMKN 7 in Bengkulu City - Ahmat Syantori; Grace Tessa Lonica Simanjuntak; M.Akbar Azim; Silvy Nopriliant; Desi Mahdalena (Universitas Dehasen Bengkulu, 2026)
21st century technological developments, especially artificial intelligence (AI) and digital literacy, are increasingly important in vocational education to improve students' work readiness. AI socialization and training activities carried out at SMKN 7 Bengkulu City aim to strengthen students' understanding of the wise and productive use of technology. Using qualitative descriptive methods through material presentation and activity-based practice, the activities lasted for 30 days involving 480 students. The results show that 96% of students participated actively and were able to understand AI concepts more concretely. Apart from being an information tool, the use of AI has been proven to encourage students' critical thinking skills through data analysis and evaluation. This activity has a positive impact in increasing students' digital literacy, technology skills and work readiness to face the industrial world.